Determining the Criticality of Li‐Excess for Disordered‐Rocksalt Li‐Ion Battery Cathodes. Issue 24 (5th May 2021) - Lee, Jinhyuk; Wang, Chao; Malik, Rahul; Dong, Yanhao; Huang, Yimeng; Seo, Dong‐Hwa; Li, Ju
Abstract: The development of Li‐excess disordered‐rocksalt (DRX) cathodes for Li‐ion batteries and interpretation through the framework of percolation theory of Li diffusion have steered researchers to consider "Li‐excess" ( x > 1.1 in Li x TM2− x O2 ; TM = transition metal) as being critical to achieving high performance. It is shown that this is not necessary for Mn‐rich DRX‐cathodes demonstrated by Li1.05 Mn0.90 Nb0.05 O2 and Li1.20 Mn0.60 Nb0.20 O2, which both deliver high capacity (>250 mAh g −1 ) regardless of their Li‐excess level. By contextualizing this finding within the broader space of DRX chemistries and confirming with first‐principles calculations, it is revealed that the percolation effect is not crucial at the nanoparticle scale. Instead, Li‐excess is necessary to lower the charging voltage (through the formation of condensed oxygen species upon oxygen oxidation) of certain DRX cathodes, which otherwise would experience difficulties in charging due to their very high TM‐redox potential. The findings reveal the dual roles of Li‐excess – modifying the cathode voltage in addition to promoting Li diffusion through percolation – that must be simultaneously considered to determine the criticality of Li‐excess for high‐capacity DRX cathodes. Abstract : Development of disordered‐rocksalt (DRX) Li‐ion cathodes based on the percolation theory of Li diffusion has steered researchers to consider "Li‐excess" ( x > 1.1 in Li x TM2− x O2 ; TM = transition metal) as being critical for high performance. It is demonstrated that Li‐excess benefits are chemistry specific at the nanoparticle scale and that DRXs made with low‐voltage TMs do not require Li‐excess for high capacity.